2008
DOI: 10.2140/gtm.2008.13.147
|View full text |Cite
|
Sign up to set email alerts
|

Basis-conjugating automorphisms of a free group and associated Lie algebras

Abstract: Let F n = x 1 , . . . , x n denote the free group with generators {x 1 , . . . , x n }. Nielsen and Magnus described generators for the kernel of the canonical epimorphism from the automorphism group of F n to the general linear group over the integers. In particular among them are the automorphisms χ k,i which conjugate the generator x k by the generator x i leaving the x j fixed for j = k. A computation of the cohomology ring as well as the Lie algebra obtained from the descending central series of the group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(118 citation statements)
references
References 22 publications
3
115
0
Order By: Relevance
“…Comparing Alexander polynomials of two poly-free groups Cb + 4 and P 4 we prove that these groups are not isomorphic, despite the fact that they have a lot of common properties. This answers the question of Cohen-Pakianathan-Vershinin-Wu from [8]. The questions of linearity of subgroups of Aut(F n ) are considered.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Comparing Alexander polynomials of two poly-free groups Cb + 4 and P 4 we prove that these groups are not isomorphic, despite the fact that they have a lot of common properties. This answers the question of Cohen-Pakianathan-Vershinin-Wu from [8]. The questions of linearity of subgroups of Aut(F n ) are considered.…”
mentioning
confidence: 60%
“…However, in the case of the group Cb + n , the situation is different. Lie algebras and cohomology rings of groups Cb + n were described in [8]. It was also shown in [8] that the group Cb + n is isomorphic to the pure braid group P n for n = 2, 3.…”
Section: The Group Cbmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cohen-Pakianathan [3,4], Farb [5] and Kawazumi [12] independently showed that the abelianization of IA n is a free abelian group, and the Magnus generators above induce a basis of it. More precisely, they showed…”
Section: Notation and Conventionsmentioning
confidence: 99%
“…It was conjectured that A n (k) = A n (k) for each k ≥ 1 by Andreadakis, who showed that A 2 (k) = A 2 (k) for each k ≥ 1 and A 3 (3) = A 3 (3) in [1]. Now, we have A n (2) = A n (2) due to Cohen-Pakianathan [3,4], Farb [5] and Kawazumi [12]. (See (3) below.)…”
Section: Introductionmentioning
confidence: 98%